1996
DOI: 10.1002/(sici)1099-1573(199612)10:8<692::aid-ptr928>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Antimalarial Active Principles ofSpathodea campanulata Stem Bark

Abstract: Antimalarial principles of Spathodea campanulata stem bark extract were isolated and characterized. The antimalarial principles in the stem bark were 3β‐hydroxyurs‐12‐en‐28‐oic acid (ursolic acid) and two of its derivatives; 3β‐hydroxyurs‐12,19‐dien‐28‐oic acid (tomentosolic acid) and 3β,20β‐dihydroxyurs‐12‐en‐28 oic acid. This is the first report of the isolation of ursolic acid and its derivatives as antimalarial compounds

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…[205][206][207] Compound 117 has been previously reported to possess anti-plasmodial activity. 208 and in this study the compound showed an appreciable anti-plasmodial activity with an IC 50 value of 6.8 mg mL À1 at the tested concentration using CQS of P. falciparum. The lower activity of the compound as compared to the crude extract could be due to synergistic effect with other compounds, decomposition during fractionation.…”
Section: Pentacyclic Triterpenoidssupporting
confidence: 60%
“…[205][206][207] Compound 117 has been previously reported to possess anti-plasmodial activity. 208 and in this study the compound showed an appreciable anti-plasmodial activity with an IC 50 value of 6.8 mg mL À1 at the tested concentration using CQS of P. falciparum. The lower activity of the compound as compared to the crude extract could be due to synergistic effect with other compounds, decomposition during fractionation.…”
Section: Pentacyclic Triterpenoidssupporting
confidence: 60%
“…MS and MS/MS data of all the identified compounds are shown in Table S1. The chemical structure of the 11 characterized compounds, which was confirmed by comparison with existing structures [22][23][24][25][26][27]30], is shown in Table 2. Compound 5,7-dihydroxy-4-metilcoumarin was detected in this plant for the first time, through the mass spectral database mzCloud.…”
Section: Chemical Composition Of S Campanulata Fractions and Sub-fractionsmentioning
confidence: 67%
“…Data about the chemical characterization of S. campanulata are limited. Nevertheless, previous studies undertaken on the stem bark and leaves have shown the presence of phenolic acids, flavonoids, triterpenoids, iridoids, and sterols [22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Of the three triterpenes that were isolated from M. caffra and M. obtusifolia (ursolic acid, taraxerol and sawamilletin), only ursolic acid showed any appreciable anti-plasmodial activity (IC 50 6.8 μg/mL) at the concentration tested. Ursolic acid has been previously reported to possess anti-plasmodial activity [21], and its presence in M. caffra could have contributed to the observed bioactivity of the plant. The lower activity of the extracted ursolic acid (compared to the crude M. caffra extract) could indicate a synergistic effect with other compounds, decomposition during fractionation, or removal of a protective matrix.…”
Section: Resultsmentioning
confidence: 99%